Energy Routing Protocols for Energy Internet: A Review on Multi-Agent Systems, Metaheuristics, and Artificial Intelligence Approaches - Amani Fawaz; Imad Mougharbel; Kamal Al-Haddad; Hadi Y. Kanaan (IEEE Access)
The Energy Internet (EI) is transforming power networks by integrating Smart Grids (SGs), Distributed Energy Sources (DESs), and advanced communication and data technologies. This transformation increases complexity, as energy transmission evolves into a multi-source, multi-path, and multi-load system, with Peer-to-Peer (P2P) energy trading markets and Energy Routers as central drivers. As power networks grow and become more decentralized, the need for efficient and adaptive power routing protocols has become crucial to ensure their reliable and scalable management. This review focuses on energy routing strategies using multi-Agent architectures, Artificial Intelligence, and Metaheuristic optimization techniques. These approaches are well-suited to support the transformation of power networks into more distributed, dynamic, and complex systems. Spanning research from 2018 to 2024, this paper consolidates diverse studies, filling a critical gap by providing a comprehensive overview of power routing solutions for the evolving EI. It highlights key methodologies, limitations, and future research directions, offering a valuable reference for researchers.